A Methodological Framework for the Comparative Analysis of the Environmental Performance of Roadway and Railway Transport - Mintzia, Diamanto; Kehagia, Fotini; Tsakalidis, Anastasios; Zervas, Efthimios (Promet - Traffic&Transportation, 2018)
Low-carbon transport is a priority in addressing climate change. Transport is still almost totally dependent on fossil fuels (96%) and accounts for almost 60% of global oil use. Sustainable transport systems, both passenger and freight, should be economically and technically feasible, but also low-carbon and environmentally friendly. The calculation of greenhouse gas emissions in transport projects is becoming a primary target of transport companies as a part of an endeavor for low-carbon strategies to reduce the energy demand and environmental impact. This paper investigates the CO2 impact of construction and operation of the main highway and railway line infrastructure in Greece, which connects Athens and Thessaloniki, the capital and the second biggest city in Greece respectively and provides a comparative analysis in roadway and railway transport.